EMPOWERMENT THROUGH FEMALE SOLIDARITY: INTERGENERATIONAL AND INTRAGENERATIONAL BONDS IN THE PEARL THAT BROKE ITS SHELL AND THE HENNA ARTIST (Contemporary Journal of Social Science Review, 2025)
Women across the world frequently face systematic oppression and restrictive societal norms that limit their autonomy. Literature reflects women’s individual struggle and experiences within oppressive structures, but the role of female alliances in fostering empowerment remains underexplored. Despite extensive feminist literary research, there is a critical gap in examining how female alliances function as tools of strength and survival, as most studies focus on individual females’ struggles. Therefore, using Lazar’s Feminist Discourse Analysis model under the broader umbrella of Radical Feminist Theory, the current study aimed to examine female solidarity as a survival strategy in The Pearl that Broke Its Shell by Hashimi and The Henna Artist by Joshi. The findings revealed that female solidarity functions through shared experiences, emotional support, mentorship, and collective resistance, allowing women to gain strength within restrictive social structures. Through language, shared memory, and women-centered relationships, solidarity becomes a key means of empowerment across generations.